Approaches to the solution of urbanization problems. (Lösungsansätze zu Verstädterungsproblemen.) - Menck, Karl Wolfgang (My University, 1976)
The presence of some 4.000 delegates from about 15 countries showed what great interest the Conference on Human Settlements (Habitat) held by the UN in Vancouver from May 31 to June 11, 1976, has evoked in many coiuntries. This coinference in Canada which was the largest ever to be arranged by the UN deal a problem which has manifested itself all over the world. (DSE)
Keywords: Stadtentwicklung; Wohnungsbau; Bevölkerungsentwicklung; Bauwirtschaft; Konferenz; Modell; Entwicklungsland; Habitat-Konferenz; Siedlungsstruktur; Verstädterung